Trajectories of life satisfaction: Positive feedback loops may explain why life satisfaction changes in multi-year waves, rather than oscillating around a set-point - Bruce Headey; Ruud J. A. Muffels (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Long term panel data enable researchers to construct Life Satisfaction (LS) trajectories for individuals over time. In this paper we analyse the trajectories of respondents in the German Socio-Economic Panel who recorded their LS for 20 consecutive years in 1991 - 2010. Previous research has shown that at least a quarter of these respondents recorded substantial long term changes in LS (Headey, Muffels and Wagner, 2010, 2012). In this paper, bar charts of LS trajectories, and subsequent statistical analysis, show that respondents tend to spend multiple consecutive years either above and/or below their own 20-year mean level of LS. These results are contrary to set-point theory which views LS as stable, exceptfor short term fluctuations due to major life events. In the later part of the paper we attempt to explain multi-year/medium term changes in LS. We estimate structural equation models with two-way causation between LS and variables usually treated as causes of LS, including health, frequency of physical exercise, frequency of social activities/social participation, and satisfaction with work and leisure. The results are interpreted as showing positive feedback loops between these variables and LS, such that gains and losses of LS tend to be reinforced over time. The models are based on a modified concept of "Granger-causation" (Granger, 1969). The main intuition behind Granger-causation is that if x can be shown to be statistically significantly related to y in a model which includes multiple lags of y, then it can be inferred that x is one cause of y.
Keywords: 330; subjective indicators; methods